Bacteriological Profile and Antibiotic Susceptibility Patterns of Gram-negative Bacilli Isolated from Lower Respiratory Tract Infections - Divya Atray; S. Sheethal (Indian Journal of Medical Specialities)
Background: Lower respiratory tract infections (LRTIs) are one of the most frequent infections seen in humans. Bacterial etiology of these infections is one of the major causes of morbidity and mortality. The emergence of drug resistance among bacteria is increasing throughout the world causing more severe infections because of their continuous mutation and multidrug resistance nature. Objectives: This study was focused on obtaining a comprehensive insight into the Gram-negative bacillary profile of LRTIs, their prevalence, and their antibiotic susceptibility patterns. Materials and Methods: The study was conducted for a duration of 6 months. Samples were obtained from patients of all ages and both sexes presenting with symptomatology suggestive of LRTIs. Following conventional culture, the isolated organisms were identified by various preliminary identification methods and biochemical tests. Antimicrobial sensitivity testing of Gram-negative isolates was performed by standard methods as recommended by CLSI 2019. Results: Out of the 1724 LRT specimens evaluated, 307 (17.80%) were culture positive. Our study showed that Gram-negative bacilli are the predominant cause (97.70%) of LRTIs with Klebsiella pneumoniae (42%) as the major pathogen followed by Escherichia coli (31.66%), Pseudomonas aeruginosa (25.33%), and Acinetobacter baumannii (1%). Extended-spectrum beta-lactamase production was detected in 3.33% and metallo-beta-lactamase in 2% of the total GNB pathogens. Conclusion: For effective management of LRTIs, an ultimate and detailed bacteriological diagnosis along with antimicrobial susceptibility testing is required to overcome the global problem of antibiotic resistance.